ANALISIS SALURAN DISTRIBUSI KERUPUK UYEL DI PT. INDO PUTRA HARAPAN SUKSES MAKMUR KEDIRI - Navita Maharani; Sulung Anugerah (Universitas Pahlawan Tuanku Tambusai, 2022)
Distribution channel is the flow of goods from producers to agents or intermediaries or wholesalers and to the final consumer. Distribution channel is a very important part in a company. Because it will affect the decisions made by company managers. This research was conducted as a study of the distribution channel conducted by PT. Indo Putra Harapan Sukses Makmur Kediri. The research method used is qualitative. The data collection technique is literature study and field study. Field studies using observation, and interviews. The results showed that PT. Indo Putra Harapan Sukses Makmur Kediri uses 2 types of distribution channels. Direct distribution channels and indirect distribution channels. There are 3 patterns of indirect distribution channels, namely: 1) Producers, Wholesalers, Retailers, and Consumers. 2) Producers, Wholesalers, Consumers. 3) Producer, Retailers, Consumers. The most efficient distribution channel pattern is direct channel distribution Keywords: Channels, Distribution, Uyel Crackers